ISOLATES OF POLYPROPYLENE-DEGRADING BACTERIA FROM A LANDFILL - Nastiti Trikurniadewi; Ana Mariatul Khiftiyah; Silvia Kurnia Sari; Wika Ifananda; Dian Irma Suryani; Ni'matuzahroh Ni'matuzahroh (Poltekkes Kemenkes Semarang, 2022)
Polypropylene (PP) is a synthetic, heat-resistant, plastic. This quality has made it the second most commonly used in everyday life, including in disposable medical face masks. While the COVID-19 pandemic has led to an escalation of the face masks use in the last two years, their abundant waste, which is difficult to decompose naturally, can have a negative impact on the environment and human health. The purpose of this study was to obtain isolates of PP decomposing bacteria from the landfill in Ngipik, Gresik. The isolates were obtained from soil samples in the landfill. Bacterial isolates were tested for their ability to degrade PP during the 28 days of the liquid phase. The data obtained were bacterial growth data and PP degradation. There were three isolates that had the potential to decompose PP, namely NG 1, NG 2, and NG 3. It was concluded that the NG2 bacterial isolate is able to decompose PP by 0.47%. Based on the results of 16S sRNA, these three tended to be in the genus of Bacillus. The results of this study are expected to enrich the data of potential local bacteria to decompose PP obtained from Gresik landfill areas.